Elementary school curriculum - Vashist, S. R. (New Delhi : Anmol Publications, 2000)
It provides guidelines in the field of reading examine practices in outstanding elementary schools and helps in developing a programme which is best suited to local needs and circumstances.
Keywords: Education, Elementary -- Curricula; Curriculum planning